What can HR management do with emotional intelligence? - Nagy, Henrietta; Marczell-Szilágyi, Eszter; Magyar, Tímea (Serbian Journal of Management, 2023)
Emotional intelligence has been a remarkably popular topic of HR-publications since the ‘90s. Organizational effectiveness and high emotional competences at a company definitely show high correlation, but despite the obvious importance of EQ-proficiency, it still remains a question how managers (and HR) can utilize the tools that emotional intelligence offers them to increase the efficiency of their organizations. The primary research of this study is based on an extended questionnaire research aiming to get more detailed information about the real nature of human motivation (including autotelic types of motivation) by summarizing and analyzing the answers of more than one thousand respondents. The other primary research base of the study is an interview-based analysis (involving more than 70 respondents) wishing to know more about the possible interactions between significant emotional effects and the ability of human learning. The result of the study is the construction of a model frame that can help organizational managers and HR experts to review the main types of leadership methods based on psychological procedures built on emotional intelligence and the possible ways of using this knowledge to increase organizational effectiveness within the companies.
Keywords: emotional intelligence; HR management; organisational effectiveness; learning organisation